MENUMBUHKAN DAYA NALAR ( POWER OF REASON ) SISWA MELALUI PEMBELAJARAN ANALOGI MATEMATIKA - Rahayu Kariadinata (Jurnal Infinity, 2012)
Learning mathematical analogy is one alternative learning that can be applied in order to cultivate the power of reason (power of reason) students. Through mathematical analogy students are required to be able to look for similarities or relationship nature of the two concepts are the same or different by comparison, then draw a conclusion from the similitude. Thus the analogy can be used as an explanation or as the basis of reasoning. Before starting the analogy of learning mathematics, teachers should examine the ability of understanding mathematical concepts of students, because of the level of understanding of students will affect the power of reason. Tasks (problems) mathematical analogy included non-routine matter, therefore the required readiness of teachers to make it. In each question contained mathematical analogy same or different concepts, so it takes quite a lot of material. Steps to make about the mathematical analogy, are: a) assemble all the concepts in mathematics student has learned; b) Similarly stacking properties / relationships contained in any concept, and c) select materials that have a nature / relationship analogous. In this paper is given two forms of matter of mathematical analogy is the analogy of mathematical models and mathematical analogy 1 models 2. Learning mathematical analogy should be carried out after a number of concepts learned. It is better to be given in classes end for many of the concepts that have been learned by the students. Reasoning power (power of reason) the student becomes an important part in the process of learning to drive them toward their future as citizens are intelligent, which will be led by the power of reason (the brain) and not by the strength (muscle) only. As noted by former US President Thomas Jefferson (in Copi, 1978: vii), which states: "In a republican nation, Whose citizens are to be led by reason and persuasion and not by force, the art of reasoning Becomes of first importance"Â Â